Improving The Understanding of The Religion of “Syifaul Qulub” Learning Group in Lamongan District Through Nonformal Education in The Teaching of Sunday Morning - Hana Nadia (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
This study aims to explore what underlies the influence of non-formal education on the understanding of religion in “Syifaul Qulub” learning group in Lamongan Regency. The approach used is quantitative, so far the understanding of pilgrims can be involved and understand Islam. The first variable is